Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.3354/meps191153
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of invertebrate larvae to predators:how common are post-capture larval defenses?

Abstract: Predation is bel~eved to be a major source of mortal~ty for larvae of benthlc Invertebrates, but the palatab~hty of larvae commonly found In the water column has rarely been assessed Larval palatability assays were conducted by collecting live invertebrate larvae from a temperate f~e l d slte and offerlng them to a suite of common predators (the flshes Lagodon rhomboides, Leiostomus xanthurus, and Monacanthus h~s p~d u s and the hard coral Ocul~na arbuscula) By crushing larvae that were rejected intact and re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…In these taxa tradeoffs exist between defense and growth and reproduction. Bullard et al (1999) empirically observed that many pelagic larvae are chemically undefended. No young of any blue-ringed octopus have yet been examined for the presence of TTX or other evidence of chemical protection.…”
Section: Introductionmentioning
confidence: 99%
“…In these taxa tradeoffs exist between defense and growth and reproduction. Bullard et al (1999) empirically observed that many pelagic larvae are chemically undefended. No young of any blue-ringed octopus have yet been examined for the presence of TTX or other evidence of chemical protection.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical response varies strongly among species and is generally lacking among most 7 meroplankton, with morphological and physical resistance often more common features than 8 chemical defense itself (Bullard et al, 1999). Consequently, individual taxa should be considered 9 separately when assessing the role of predation on the coupling between larval-supply and 10 settlement and on overall community assemblages.…”
Section: Larval Predationmentioning
confidence: 99%
“…Food availability could also create differences in habitat quality for M. tuckeri. However, Barrett (1999) found that food was not a limiting factor in growth of a temperate monacanthid in Australia, and Bullard et al (1999) found that an Atlantic monacanthid could readily consume a wide array of available microinvertebrate prey. M. tuckeri has a broad diet including algae, detritus and invertebrates 1 , so food is likewise unlikely to be a limiting resource for this species.…”
Section: Discussionmentioning
confidence: 97%